Isolamento de leveduras do processo de produção do queijo da canastra e avaliação do potencial de fermentação do soro de leite - Andrade, Rafaela Pereira (2016)
The Canastra cheese is an artisanal Minas cheese produced for over 200 years in the region of Serra da Canastra, Minas Gerais, Brazil. This cheese is produced from raw milk inoculated with commercial curd and “pingo”. “Pingo” is an endogenous leaven derived from natural fermentation of the whey that drains from the cheese in the last 24 hours. The microorganisms present in the “pingo” are mostly bacteria, especially the bacteria from lactic acid and a few yeast. This work had the objective of isolating and identifying yeast from the “pingo”, whey, milk and canastra cheese, and evaluating its capacity for fermenting whey to generate different metabolites, such as ethanol and volatile aromatic compounds. A total of 145 isolates were purified and tested regarding their capacity to ferment lactose in synthetic medium. Of these, 39 presented the capacity of fermenting lactose and were previously grouped and identified by MALDI TOF as Kluyveromyces lactis (29), Torulaspora delbruckii (7), and Candida intermedia (3). Four isolates (Kluyveromyces lactis B10, Torulaspora delbruckii B14, B20 and B35) were more efficient in reducing the Brix when in whey fermentation trials in three different Brix (18, 14 and 12). The fermentation of whey 14 o Brix with Torulaspora delbruckii B14 resulted in the production of 24.06 g/L of ethanol, while with Kluyveromyces lactis B10 all the lactose of the whey was consumed. These yeast were used in sequential cultivation with the inoculation of Kluyveromyces lactis B10, 48 hours after inoculation with Torulaspora delbruckii B14, resulting in the production of 10.86 g/L of ethanol, 0.12 g/g of Yp/s, 23.14% of sugar conversion into ethanol and 60.32% of total sugar conversion. A total of 39 volatile aromatic compounds were identified and quantified in the fermentation, consisting of alcohols 2-methyl-1-buthanol, 3-methyl-1-buthanol and 2- phenylethanol, in the concentrations of 52.72 µg/L, 123.59 µg/L and 77.11 µg/L, respectively, 13 esters, with higher concentrations for ethyl decanoate, with 175.22 µg/L, and 9 -decanoate acetate, with 62.16 µg/L, in addition to 9 volatile acids. All aromatic compounds are relevant in the production of dairy products, which, in addition to the production of ethanol, indicates the potential of these yeasts in the context of this work.